Macroparasites at peripheral sites of infection are major and dynamic modifiers of systemic antimicrobial pattern recognition responses. Issue 10 (4th February 2013) - Friberg, I. M.; Little, S.; Ralli, C.; Lowe, A.; Hall, A.; Jackson, J. A.; Bradley, J. E.
Abstract Immune defences and the maintenance of immunological homeostasis in the face of pathogenic and commensal microbial exposures are channelled by innate antimicrobial pattern recognition receptors (PRRs) such as toll‐like receptors (TLRs). Whilst PRR‐mediated response programmes are the result of long‐term host‐pathogen or host–commensal co‐evolutionary dynamics involving microbes, an additional possibility is that macroparasitic co‐infections may be a significant modifier of such interactions. We demonstrate experimentally that macroparasites (the model gastrointestinal nematode, Heligmosomoides) at peripheral sites of infection cause substantial alteration of the expression and function of TLRs at a systemic level (in cultured splenocytes), predominantly up‐regulating TLR2, TLR4 and TLR9‐mediated cytokine responses at times of high standing worm burdens. We consistently observed such effects in BALB/c and C57BL/6 mice under single‐pulse and trickle exposures to Heligmosomoides larvae and in SWR and CBA mice under single‐pulse exposures. A complementary long‐term survey of TLR2‐mediated tumour necrosis factor‐alpha responses in wild wood mice (Apodemus sylvaticus) was consistent with substantial effects of macroparasites under some environmental conditions. A general pattern, though, was for the associations of macroparasites with TLR function to be temporally dynamic and context‐dependent: varying with different conditions of infection exposure in the field and laboratory and with host genetic strain in the laboratory. These results are compelling evidence that macroparasites are a major and dynamic modifier of systemic innate antimicrobial responsiveness in naturally occurring mammals and thus likely to be an important influence on the interaction between microbial exposures and the immune system.